READING THEORIES AND READING COMPREHENSION - Ngabut, Maria Novary (Journal on English as a Foreign Language (JEFL), 2015)
In this article several reading theories in their relations to reading comprehension teachers and lecturers of English need to know are reviewed. At the theory level, three other Models of Reading, namely Bottom-Up, Top-Down, and Interactive are previously discussed to the Schema Theory. In reviewing the reading comprehension, the history of reading instruction, types and purposes of reading, and cognitive reading skills are discussed. Finally, it reviews six variables involved in the comprehension of English texts.Keywords: models of reading, schema theory, comprehension, background knowledge